Older married couples' sexual expression: A dyadic latent class analysis. (December 2020) - Warner, David F.; Lyons, Heidi A.
Many older adults continue to engage in sexual behavior, most often in the context of long-term marriages. Prior studies have tended to examine older adults' sexual behavior, desires and motivations separately. Thus, there remain considerable gaps in our understanding of the multifaceted-nature of older couples' sexual expression. Using dyadic latent class analysis and data on 953 heterosexual couples in long-term marriages from Wave 2 of the National Social Life, Health, and Aging Project (NSHAP), we describe configurations of couples' sexual expression. Four latent classes were identified. Within each latent class, couples were largely in agreement about their sexual behaviors, but husbands consistently expressed greater desire and motivation than their wives. In the highest engagement class, couples reported more frequent and wide-ranging activities (vaginal sex, oral sex, intimate touching), more frequent thinking about sex, greater satisfaction with their amount of sexual activity, and placed more importance on sex as part of their lives. In the lowest engagement class, both spouses indicated no sexual activity in the past year, but neither spouse was content with this situation even as both agreed sex was not an important part of life. Demographic, relational, and health factors were associated with membership in different classes. Health factors—especially sexual difficulties—were most predictive, with husbands' health more associated with latent class membership than wives' health. Given the complex and multifaceted nature of sexual expression among older married couples, geriatricians and other health practitioners should provide care that recognizes a wider array of activities and the potential for unmet need. Sexual expression is an important component of older adults' health and well-being.